Serum soluble DR5 predicts mortality risk in patients with HBV-related hepatocellular carcinoma - Liang, Jiaqi; Feng, Ying; Liu, Yao; Shi, Ke; Zhou, Guiqin; Liu, Long; Liu, Yaxin; Qiao, Kexin; Liu, Wen; Wang, Xianbo (Frontiers in Oncology, 2022)
Introduction Death receptor 5 (DR5) is significantly upregulated in various human tumor tissues; however, the relationship between serum levels of soluble DR5 (sDR5) and the mortality risk of hepatocellular carcinoma (HCC) is not understood. Our aim is to investigate the prognostic value of serum sDR5 in HCC patients. Methods A total of 170 patients with HBV-HCC were recruited, with 82 and 88 patients as derivation and validation cohorts, respectively. sDR5 levels were analyzed using ELISA. The predictive factors for mortality were selected using LASSO regression analysis. Cox regression analysis was used to analyze the independent factors affecting mortality in 2 years. A nomogram based on the interquartile range of the sDR5 values predicted mortality rates. Results Serum sDR5 level was identified as an independent risk factor for mortality in patients with HBV-HCC. The 2-year cumulative mortality rates of HBV-HCC were 10, 28.57, 38.10, and 95% across the sDR5 quartiles, respectively (p < 0.001). The sDR5 had an AUROC of 0.851 (95% CI: 0.755–0.920) in the derivation cohort. When the cut-off value was 30.06pg/mL, the AUROC of sDR5 was 0.778 (95% CI 0.677–0.860) in the validation cohort. The calibration curves fit well, and the decision curves showed that sDR5 had a high standardized net benefit. sDR5 predicted the prognosis of HBV-HCC patients most accurately. Further, serum sDR5 level was significantly positively associated with BCLC stage and the presence or absence of ascites. Conclusion sDR5 showed high predictive accuracy in patients with HBV-HCC; thus, it is considered a new serological biomarker.